Distinct subpopulations of DN1 thymocytes exhibit preferential γδ T lineage potential - Oh, Seungyoul; Liu, Xin; Tomei, Sara; Luo, Mengxiao; Skinner, Jarrod P.; Berzins, Stuart P.; Naik, Shalin H.; Gray, Daniel H. D.; Chong, Mark M. W. (Frontiers in Immunology, 2023)
The αβ and γδ T cell lineages both differentiate in the thymus from common uncommitted progenitors. The earliest stage of T cell development is known as CD4-CD8- double negative 1 (DN1), which has previously been shown to be a heterogenous mixture of cells. Of these, only the CD117+ fraction has been proposed to be true T cell progenitors that progress to the DN2 and DN3 thymocyte stages, at which point the development of the αβ and γδ T cell lineages diverge. However, recently, it has been shown that at least some γδ T cells may be derived from a subset of CD117- DN thymocytes. Along with other ambiguities, this suggests that T cell development may not be as straightforward as previously thought. To better understand early T cell development, particularly the heterogeneity of DN1 thymocytes, we performed a single cell RNA sequence (scRNAseq) of mouse DN and γδ thymocytes and show that the various DN stages indeed comprise a transcriptionally diverse subpopulations of cells. We also show that multiple subpopulations of DN1 thymocytes exhibit preferential development towards the γδ lineage. Furthermore, specific γδ-primed DN1 subpopulations preferentially develop into IL-17 or IFNγ-producing γδ T cells. We show that DN1 subpopulations that only give rise to IL-17-producing γδ T cells already express many of the transcription factors associated with type 17 immune cell responses, while the DN1 subpopulations that can give rise to IFNγ-producing γδ T cell already express transcription factors associated with type 1 immune cell responses.